INFRASTRUKTUR PUBLIK DAN PERCEPATAN PEMBANGUNAN DI INDONESIA - Rudi Alamsyah; M. Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThis study aims to find out and analyze the budget in accelerating economic growth in Indonesia. The method used in this study is a quantitative analysis method using the Autoregressive Distributed Lag (ARDL) model. The data used are time series data from 1968 to 2017. The variables used are economic growth, spending and exchange as a control variable. The results showed that infrastructure spending had a negative influence on economic growth in the short term and from the results of the study. Based on the findings, this research recommended to use infrastructure spending wisely to provide the infrastructures. The infrastructure, later on will safeguard the economic growth in the futureKeywords: Economic growth, infrastructure spending, ARDL, Indonesia